"Kei A Koe, Chair!" – The Norms of Tikanga and the Role of Hui as a Māori Constitutional Tradition - Stephens, Māmari (Victoria University of Wellington Law Review, 2022)
Hui and hui rūnanga, Māori decision-making gatherings, are vital in Māori constitutionalism. Hui demonstrate the practical exercise of tikanga Māori. There is a set of relatively stable Māori legal norms, derived from tikanga Māori, that can be seen at work in such hui-based decision-making. These norms (mana, tapu, whakapapa, whanaungatanga and rangatiratanga) serve to strengthen and demonstrate group processes. They arguably do not establish merely optional guidelines for group behaviour; they can serve to constrain decision-making. A case study set in a hui in a modern Māori urban context serves to demonstrate the exercise of such Māori legal norms in civic decision-making.